Reliability Assessment Based on GO Method of Metro Traction System - Qi Gong; Bingzhi Chen; Yonghua Li; Pengpeng Zhi (Advances in Materials Science and Engineering)
In order to improve the reliability of the metro traction system (MTS), the whole life cycle of metro vehicles can be operated safely and reliably. A reliability assessment method based on the GO method of the MTS is proposed. In this paper, the reliability assessment is completed without operation service failure of the metro vehicle. The maintainability and shutdown correlation of many electrical components in the MTS are considered. An accurate algorithm with shared signals is used. Then the quantitative and qualitative reliability assessment of the system is achieved with the goal of traction system providing traction for the vehicle. The evaluation identifies the weak links of the system. Comparing the completely independent quantitative calculation result of each component with the accurate quantitative calculation results, it is found that the complex correlation in the repairable system has an important effect on the reliability of the system. A comparative analysis is performed on the calculating results of the GO method and fault tree analysis (FTA) method. The results demonstrate that the reliability analysis of the MTS by the GO method is feasible and reasonable. The principle of the method is simple and the logic is clear. It can not only objectively reflect the working process of the MTS, but also fully characterize the complex correlation with shut down fault in the MTS. The qualitative assessment results of the system show that the cut set probability of the pantograph is the highest, which should be the focus of the MTS.